DEVELOPMENT OF U-CHANNEL SCREW JACK FOR VEGETABLE OIL EXTRACTION (Nigerian Journal of Technology, 2017)
A U-channel screw jack for extracting vegetable oil was developed through design (with Solid works–Computer Aided Design (CAD)) and fabrication processes. A factorial experiment in a Randomized Complete Block Design (RCBD) was used to investigate the effect of heating temperature (50, 60 and 70°C) and heating time (5 and 10 min) on the performance of the machine in terms of oil yield, extraction efficiency and extraction loss with groundnut as the feedstock. Results of the machine design for some of the machine components gave the following values: U-channel structural frame made of mild steel (80 x 160 x 650 mm), compression cap (70 mm) and heater band(3.5kW). Also, the performance evaluation of the machine showed that increase in heating temperature (50 to 70°C) and heating time (5 to 10 min) did not cause the oil yield, extraction efficiency and extraction loss to increase beyond 30%, 48% and 15% respectively. Generally, decrease in oil yield, extraction efficiency and extraction loss occurred at the heating temperature of 70 oC irrespective of the heating time. For future works, other machine and feedstock factors should be incorporated into the performance evaluation process. Also, automation of the machine is recommended.   http://dx.doi.org/10.4314/njt.v36i3.43